Development Guidance Practical of Problem Based Learning Chemistry Guide for Coloid Materials for Class XI SMA/MA - Nadia Khairunnisa; Effendi Effendi (Universitas Negeri Padang, 2023)
The research on developing a chemistry practicum guide based on problem based learning colloid material for class XI SMA students aims to determine the effectiveness of the developed practicum guide. Research and Development (R&D) is this type of research using the Plomp model. The Plomp model has 3 stages, including: 1) preliminary research, 2) prototype stage, 3) evaluation stage. The validity of this practicum guide was tested by two chemistry lecturers from FMIPA UNP and two chemistry teachers from SMAN 2 Rambatan and SMAN 1 Rambatan using a validation instrument. The validity of the validators was analyzed using the Aiken's V formula. The results of the construct validity analysis with Aiken's V average score of 0.84 were included in the very high validity category and the content validity 0.86 also included in the very high validity category. The data obtained indicate that the PBL-based colloid practicum guide for class XI SMA/MA students is valid and practical.